PIC microcontroller projects in C - Ibrahim, Dogan (Elsevier Science, 2014)
Microcomputer Systems -- mikroC Pro for PIC Programming Language -- MPLAB X IDE and MPLAB XC8 C Programming Language -- Microcontroller Program Development -- Simple PIC18 Projects -- Intermediate PIC18 Projects -- Advanced PIC18 Projects